Strange possession [large type] - Garlock, Dorothy (Center Point Pub., 2009)
Kelly gladly left her beloved Alaska to move to Boston and marry Jack. Once there, she learned that Jack was actually Johathan Templeton III, a Boston Brahmin. Faced with a chilly reception from his family and his sudden possessiveness, Kelly fled back to her Alaskan home. When Jack tracks Kelly back to her northern home, she has to wonder whether he is back to reclaim the wife that he loves, or to seek revenge for her desertion?